2017
DOI: 10.17722/ijme.v9i2.367
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Non Performing Loans: Evidence from Sri Lanka

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Other studies use the capital ratio (capital-to-assets) or its amount of capital as internal determinants of bank risk, (Fungacova & Weill, 2012;Horvath, Seidler, & Weill, 2014;Tan, 2016). The relationship between a bank's capital and its NPLs go in opposite directions; that is, an increase a bank's NPLs would negatively influence the value of its assets and, thus, the earnings that reflect on its capital, (Kumarasinghe, 2017).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Other studies use the capital ratio (capital-to-assets) or its amount of capital as internal determinants of bank risk, (Fungacova & Weill, 2012;Horvath, Seidler, & Weill, 2014;Tan, 2016). The relationship between a bank's capital and its NPLs go in opposite directions; that is, an increase a bank's NPLs would negatively influence the value of its assets and, thus, the earnings that reflect on its capital, (Kumarasinghe, 2017).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Some studies have also focused on identifying the economic factors affecting non-performing loans, such as Khemraj and Pasha (2009); Espinoza and Prasad (2010); Adebola et al (2011); Hsing (2014); Dimitrios et al (2016); Kumarasinghe (2017); Malimi (2017); Adusei (2018). Khemraj and Pasha (2009) identified the determinants of nonperforming loans in Ghana's banking sector.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Also, the unemployment rate, real interest rate and personal taxes had a positive impact on these loans. Kumarasinghe (2017) finds out that among six economic determinants, GDP growth rate and export growth are important in determining the level of troubled loans in Sri Lankan banking sector. The study revealed that the relationship of GDP with non-performing loans was positive and inconsistent with the majority of empirical results in previous literature.…”
Section: Previous Studiesmentioning
confidence: 99%